Patient-centered care in lung cancer: exploring the next milestones - Ben-Arye, Eran; Samuels, Noah (Translational Lung Cancer Research; Vol 4, No 5 (October 28, 2015): Translational Lung Cancer Research (Lung Cancer Diagnostics and Treatments 2015: A Renaissance of Patient Care), 2015)
Abstract: In this editorial, the authors comment on a recently published review paper by Molassiotis et al. on the developments made over the past 40 years in supportive care for patients with lung cancer. During this period, a paradigm shift promoting patient-centered care (PCC) has led to an important change in the approach of supportive cancer care, from a purely disease-centered approach, measuring survival-related outcomes, to recognizing the importance of quality of life outcomes as well. This change of understanding in supportive and palliative care for patients with lung cancer can be further advanced through the understanding that there is a need to address bio-psycho-spiritual concerns and health belief models, within the context of the family socio-cultural environment, for both patients and their caregivers. There is also a need to address the psycho-spiritual effects of cancer on those health care professionals treating patients with lung cancer, in order to reduce compassion fatigue and increase resilience. Future directions for supportive care for patients with lung cancer may include the development of a patient-tailored treatment approach, assisted by the integration of a multidisciplinary team of health care providers and evidence-based complementary medicine practices, within conventional supportive care practice.